STUDI PELAKSANAAN SISTEM INFORMASI AKUNTANSI DALAM MENUNJANG MANAJEMEN STRATEGI (Pada PT Telkom Persero, Tbk Divisi Regional III Jawa Barat dan Banten) - Sri Fadilah (Program Magister Akuntansi Unsyiah, 2008)
Basically, accounting information system represents the integration from various system of transaction processing which exists in a company in forming a network in course of data processing that consisted of many kinds procedure to produce the information for the interested parties. This research tries to describe the execution of accounting information system in supporting strategy management. The method of research that is used is descriptive method analysis and case study as well. This research is conducted at PT.TELKOM (Persero), Tbk Divre III of West Java and Banten. The results show that the application of accounting information system has adequate result, totally score is 604 or 80,53% while the rest represents the weakness of existing accounting information system. Variable of strategy management obtains result 473 or 75,68% and it also adequate, the rest represents the weakness of strategy management. Keywords : accounting information system, strategy management